Investigating the effect of the protection, dignity and security of women bill in reducing social and family violence - Namdar, Saeed; Seyfi, Anahita; Goldouzian, Iraj (Applied Family Therapy Journal (AFTJ), 2021)
Aim: One of the important issues of human rights is the issue of violence against women. Due to the fact that dealing with all forms of violence is important, but domestic violence is the most important example of violence, the focus of governments and actions due to its prevalence in the countries of the world and due to the serious physical and mental harm it causes to women. There are solutions in both domestic and international fields. Violence actually includes any kind of physical, mental, sexual violence, etc. in the family and society, Investigating the effect of the protection, dignity and security of women bill in reducing social and family violence. Methods: The method of this article is descriptive. Results: The results of the article indicate this, in case of the approval and implementation of the bill for the protection of dignity and ensuring the safety of women through measures such as the establishment of a women's protection fund, a special unit for women's security in police stations, the criminalization of blood, and the use of the capacity of some agencies. And the institutions to ensure the safety of women in the bill for preserving the dignity and ensuring the safety of women, criminalizing any type of violence in the bill,... can be effective and useful in reducing violence in the family. In case of the final approval of the bill for preserving the dignity and ensuring the security of women against violence in the parliament. Conclusion: the convicted person cannot pay the ransom of the victimized woman, a fund is foreseen to pay the damages of the women. In this bill, certain innovations are introduced such as criminalization of certain behaviors that have been criminalized so far. It didn't seem to exist.